Hubungan Self Efficacy dengan Penyesuaian Diri Siswa Kelas XI IPS SMA Negeri 8 Medan Saat Pembelajaran Tatap Muka Terbatas - Sri Manisya; Nur Arjani (INDONESIAN COUNSELING AND PSYCHOLOGY, 2022)
This study aims to find out how the relationship between self-efficacy and self-adjustment of class XI IPS students at SMA Negeri 8 Medan during face-to-face learning is limited. This research uses quantitative methods with correlational research types. The population of this research is the students of class XI IPS SMA Negeri 8 Medan T.A 2022/2023, totaling 108 students, and the number of samples in this study is as many as 85 students with a sampling technique that is Simple Random Sampling. The instrument used is a Likert scale related to self-efficacy and self-adjustment with a reliability coefficient on the self-efficacy scale of 0.899 and self-adjustment of 0.908. The collected data was then analyzed using Product Moment Correlation analysis. The results in this study show that the self-efficacy of class XI IPS students at SMA Negeri 8 Medan is classified as good with a percentage of 20%, 57.6% is sufficient, and 22.4% is low. From the results of the correlation test, it is known that the Pearson correlation coefficient (r) is 0.360 with a sign (p) of 0.001, which means that there is a positive and significant relationship between self-efficacy and self-adjustment. The coefficient of determination (r2) in this study is 0.130, which indicates the contribution of the self-efficacy variable to self-adjustment is 13%. Thus, it can be concluded, the results of the hypothesis which states that there is a relationship between self-efficacy and self-adjustment when face-to-face learning is limited, are accepted.